İran Meclis Kütüphanesi 17805 nolu türkçe şiir mecmuası (vr. 5b – 42b ) (inceleme – metin) - Burhanlı, Melis (My University, 2019)
Bu çalışmada İran Meclis Kütüphanesi 17805 numaraya kayıtlı olan Mecmū‘a-i Eş‘ârıTürkȋ’nin transkripsiyonlu metni oluşturulmuş ve incelemede bulunulmuştur. Tamamı 84varak olan mecmuanın 5b – 42b varakları arası çalışmamızı oluşturmaktadır. Alışılmışınaksine elimizdeki mecmua bir nazire veya bir gazel mecmuası değil musammatlarmecmuasıdır. İçinde 120 tane de kıt‘a bulunmaktadır.

In this study, the transcribed text of Mecmȋ‘a-i Eş‘âr-ı Türk, which is registered tothe Iranian Library with the number 17805, has created and examined. Our study consists ofthe pages from 5b to 42b of the complete 84 pages. Contrary to the usual, the magazine weexamine is not a nazire or a ghazal magazine, instead it consists of expanded poetry(musammat). The magazine is also composed of 120 verses.
Keywords: Collected Poems (Divan); Divan; Expanded Poetry (Musammat); Iran; İran; Mecmua; Musammat Magazine; Poetry; Şiir